2019
DOI: 10.1029/2019jb017643
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low‐Frequency Earthquakes in Broadband Random Time Sequences: Are They Independent Events?

Abstract: Low‐frequency earthquakes (LFEs) are detected primarily from continuous seismograms using a matched‐filter technique with an impulsive template waveform in a relatively narrow frequency band. However, this method can also detect events from some kinds of random time sequences without clearly isolated events. Here this fact is demonstrated via simple numerical simulations using the synthetic moment accelerations from a model of broadband slow earthquake, the Brownian slow earthquake (BSE) model, and a totally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
(84 reference statements)
2
22
0
Order By: Relevance
“…The present study clearly shows that the stacked LFE waveforms include continuous signals that range from the LFE and tremor frequency bands (> 1 Hz) to the VLFE frequency band (0.01-0.10 Hz). This is consistent with results for LFE families in the Cascadia subduction zone for periods of < 16 s (Ide 2019). The broader frequency range in the present study is due to the large number of stacked signals, the high sensitivity of the tiltmeters at lower frequencies, and quiet observational conditions at the bottom of the Hi-net boreholes.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The present study clearly shows that the stacked LFE waveforms include continuous signals that range from the LFE and tremor frequency bands (> 1 Hz) to the VLFE frequency band (0.01-0.10 Hz). This is consistent with results for LFE families in the Cascadia subduction zone for periods of < 16 s (Ide 2019). The broader frequency range in the present study is due to the large number of stacked signals, the high sensitivity of the tiltmeters at lower frequencies, and quiet observational conditions at the bottom of the Hi-net boreholes.…”
Section: Resultssupporting
confidence: 92%
“…Its slope, ω, is almost constant, and the deviation from this constant slope can be explained by the error. The results from LFEs in Cascadia (Ide 2019) are also plotted in Fig. 4 to highlight the high degree of consistency between these two studies.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…For example, spatiotemporal coincidence of LFTs and very low frequency earthquakes (VLFEs; e.g., Yamashita et al, 2015) and another type of slow earthquake has been observed in the Hyuga-nada region (Yamashita et al, 2015) and the Nankai subduction zone (Kaneko et al, 2018;Toh et al, 2018). Such a relationship between different types of slow earthquake phenomena suggests that this series of different dominant frequencies is a united broadband phenomenon (Ide, 2008;Ide, 2019), and it is important to use as many types of slow earthquakes to detect the broadband phenomenon and their spatiotemporal associations.…”
Section: Introductionmentioning
confidence: 99%